The Role of Contexts in the Construction of Academic Identity in Selected South African Universities - Matsepe, David; Maluleke, Mugwena (International Journal of Criminology and Sociology, 2021)
Using qualitative interviews and document analysis, that is, national and institutional policies, the study is embedded on the assumption that the purpose of the academic career is knowledge creation, dissemination, and the acquisition and promotion of high-level skills that contribute to scholarship and the support of the economy of knowledge. This implies that academics create knowledge in pursuit of the academic career to develop scholarship. Given the identity-subjectivity-agency theory, the study set out to examine the global and local contexts or dynamics that affect the academic career in constructing academic identity and how they apply to the South African higher education landscape. We argue that the legacy of apartheid affected academic careers differently as higher education institutions were divided, separated, and segregated along racial lines with different purposes. They shaped the roles of academics in different ways, with some enjoying academic freedom and autonomy while some are operating as public servants. Moreover, university academic staff should be encouraged and enabled to advance knowledge. Thus, the study recognizes the need for high-level skills and knowledge creation, which require greater attention to the nature of academic careers.